Analysis of Hazardous and Toxic Solid Medical Waste Management at Bengkalis Regency Public Health Center, 2022 - Lamin Lamin; Oktavia Dewi; Yessi Harnani; Herniwanty Herniwanty; Endang P.R (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze hazardous and toxic solid medical waste management at Bengkalis Regency Public Health Center in 2022. This study uses a qualitative type with a phenomenology research design. This research is conducted at the Damon Inpatient Public Health Center, the Selat Baru Inpatient Public Health Center, and the Pematang Duku Non-Inpatient Public Health Center, Bengkalis Regency. The time of the research will be from May to June 2022. The main informants are Environmental Health Officers and Nurses. Supporting informants are Cleaning Service. The key informant is the Head of the Public Health Center. Collecting data using the method of observation and in-depth interviews. Data processing is done using data triangulation. The results show that the implementation of waste management started from the stages of sorting, collecting, storing, transporting, but for the stage of destruction carried out by a third party. Suggestions to the Public Health Center to apply for ownership of the incinerator to the health Office and complete training for human resources in waste management.